Enhancing Solar Cell Performance: The Impact of Microstructure in Nanostructured Perovskites - Kumar, Swarup; Neidhe, Md Musfiqur Rahman; Ahmed, Faisal; Hasan, Md Mehedi (Peneliti Teknologi Teknik Indonesia, 2025)
A revolutionary development in solar cell technology, nanostructured perovskites have the potential to greatly improve stability and power conversion efficiency (PCE). The contribution of microstructure, including defect passivation, surface morphology, crystallinity, and grain size, to perovskite solar cell (PSC) performance optimization is evaluated in this paper. Through nanoscale optimization of these microstructural characteristics, scientists may enhance light absorption, minimize recombination losses, and optimize charge transfer, all of which contribute to increased efficiency. More versatility in bandgap engineering for a range of applications is made possible by the distinct optoelectronic properties of perovskites in conjunction with the benefits of nanostructuring. The endurance of nanostructured perovskites under environmental pressures and the scalability of production techniques are two issues that persist despite these developments. It is essential to overcome these obstacles in order to commercialize PSCs. Potential future developments for lead-free perovskite substitutes and the incorporation of nanostructured materials into hybrid solar systems are also examined in this study. Key results, ramifications, and opportunities for future advancements in nanostructured perovskites for solar energy technology are highlighted in this study, which summarizes the present status of research in this area. The review process aims to summarize current developments in the area and pinpoint the crucial problems that need to be resolved for wider acceptance.